Relationship between Emotional Intelligence and Commitment to Change among Senior Administrative and Diplomatic Service (ADS) Officers in Malaysia - Ramly, Mohd Sabri; Mansor, Mahaliza (International Business Education Journal, 2017)
The purpose of this study is to investigate the relationship between emotional intelligence and commitment to change among senior Administrative and Diplomatic Service (ADS) officers attached to the federal government ministries in Putrajaya/Kuala Lumpur. The data were collected in a form of questionnaire where a total of 360 senior officers participated in this research. The measurements used comprised the Wong and Law Emotional Intelligence Scale (WLEIS) by Wong and Law (2002) and Commitment to Change by Herscovitch and Meyer (2002). The result of multiple regression analysis showed that one dimension of emotional intelligence namely self-emotion appraisal has a positive relationship with all dimensions of commitment to change. Whereas, all dimensions of emotional intelligence were found to have a positive relationship with one dimension of commitment to change namely the affective commitment to change. Thus, it was noted in this study that the emotional intelligence was found as an important factor in enhancing the level of commitment to change among senior ADS officers. This finding would serve as an indicator to the high-level management of civil service to take into account the element of emotional intelligence especially in upskilling ADS officers’ emotional intelligence competencies.